Design of novel graded bone scaffolds based on triply periodic minimal surfaces with multi-functional pores - Lai, Rongwu; Jiang, Jian; Huo, Yi; Wang, Hao; Bosiakov, Sergei; Lyu, Yongtao; Li, Lei (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundVarious mechanical and biological requirements on bone scaffolds were proposed due to the clinical demands of human bone implants, which remains a challenge when designing appropriate bone scaffolds.MethodsIn this study, novel bone scaffolds were developed by introducing graded multi-functional pores onto Triply Periodic Minimal Surface (TPMS) structures through topology optimization of unit cell. The performance of these scaffolds was evaluated using finite element (FE) analysis and computational fluid dynamics (CFD) method.ResultsThe results from FE analysis indicated that the novel scaffold exhibited a lower elastic modulus, potentially mitigating the issue of stress shielding. Additionally, the results from CFD demonstrated that the mass transport capacity of the novel scaffold was significantly improved compared to conventional TPMS scaffolds.ConclusionIn summary, the novel TPMS scaffolds with graded multi-functional pores presented in this paper exhibited enhanced mechanical properties and mass transport capacity, making them ideal candidates for bone repair. A new design framework was provided for the development of high-performance bone scaffolds.